Odpowiedzi

2010-01-11T13:26:04+01:00
A)2x +9y=-9
-3x+3y=8

2x=-9-9y
3y=8+3x

2x=-9-9y
y=8/3+x


2x=-9-9(8/3+x)
y=8/3+x

2x=-9-24-9x
y=8/3+x

2x+9x=-33
y=8/3+x

x=-33/11=-3
y=8/3+(-3)

x=-3
y=2i2/3-3

x=-3
y=-1/3


b) 2x+3y=4
8x-5y=-1

2x=4-3y
-5y=-1-8x

x=2-3/2y
-5y=-1-8(2-3/2y)

x=2-3/2y
-5y=-1-16+12y

x=2-3/2y
-5y-12y=-17

x=2-3/2y
-17y=-17

x=2-3/2y
y=1

x=2-3/2*1
y=1

x=2-3/2
y=1

x=1/2
y=1


c)8x-6y=10
7x+y=5

8x=10+6y
y=5-7x

8x=10+6(5-7x)
y=5-7x

8x=10+30-42x
y=5-7x

8x+42x=40
y=5-7x

50x=40
y=5-7x

x=4/5
y=5-7(4/5)

x=4/5
y=5-5i3/5

x=4/5
y=-3/5